Strategy for managing both high strength and large ductility in structural materials–sequential nucleation of different deformation modes based on a concept of plaston. (May 2020) - Tsuji, Nobuhiro; Ogata, Shigenobu; Inui, Haruyuki; Tanaka, Isao; Kishida, Kyosuke; Gao, Si; Mao, Wenqi; Bai, Yu; Zheng, Ruixiao; Du, Jun-Ping
Abstract: Based on recent findings in ultrafine grained metals, we proposed a strategy for overcoming the strength-ductility trade-off in structural metallic materials. Sequential nucleation of different deformation modes, such as unusual slip systems, deformation twinning, martensitic transformation, etc., would regenerate strain-hardening ability of the material, leading to high strength and large tensile ductility. For discussing the activation of different deformation modes in atomistic scales, the concept of plaston which considered local excitation of atoms under singular dynamic fields was proposed. Graphical abstract: Image, graphical abstract